NATURAL REGENERATION OF Eusideroxylon Zwageri T. et B. AT GUNUNG MERATUS PROTECTION FOREST EAST KALIMANTAN - INDONESIA - Riskan Effendi (Indonesian Journal of Forestry Research, 2004)
A study on the natural regeneration  of Eusideroxylon Zwageri T et B, a native and multi purpose iron  wood  tree  species,  was  conducted   at the  Protection   Forest  of  Gunung   Meratus,  East Kalimantan, Indonesia.   As many as lS  mature  trees with  diameter  more  than 20 cm at breast height (1.30   m) were chosen for this study.  The amount of natural regeneration  found under  tree crown projection, were classified into  four height  classes:  less  than  SO cm, SO  -  100 cm, 100 - lSO cm and more  than  1SO   cm.   The  result showed that most of  the natural  regeneration  were in the SO  -100 cm height class, as many as   S8.7  %. Average number  of  natural  regenerations was 69.2    wildings  per tree ranging between 17  to 161. Such amount of natural regeneration  will compete  for their life and many of them will die in the competition  for food and light. Therefore some  of  those natural regenerations  especially the trees with more than 20 wildings may be used for planting stock  procurement  in the form of wildings without soil, wildings with soil, and stump